Pengaruh Iklim Organisasi Terhadap Kualitas Kerja Pegawai Di Sekolah Menengah Kejuruan (Smk) Negeri 1 Batudaa Kabupaten Gorontalo - B. Moha, Reyke Renaldo; Sakir, Mochamad; Dunggio, Swastiani (Program Studi Ilmu Pemerintahan, 2024)
Abstract This research aims to determine the magnitude of the influence of organizational climate on the quality of employee work at State Vocational School (SMK) 1 Batudaa, Gorontalo Regency. In the educational context, organizational climate is an important factor that can influence employee performance and productivity. Using a quantitative approach and survey methods, this research involved 37 people as a sample represented from various backgrounds at the institution. The use of simple regression analysis as a data analysis method allows researchers to determine the extent to which the relationship between organizational climate variables and employee work quality can be measured statistically. The results of the research show that organizational climate influences the quality of work of employees at State Vocational School (SMK) 1 Batudaa, Gorontalo Regency, with a coefficient value of 0.713 or 71.3%. This figure shows that more than two-thirds of employee work quality can be explained by organizational climate factors, which include aspects such as communication, managerial support, and work culture. These results indicate that organizational climate makes a significant contribution to the quality of work of teachers and education personnel, which in turn has an impact on the effectiveness of learning in schools. Thus, it is important for school management to create and maintain a positive organizational climate so that employees can work optimally and achieve the expected educational goals. This research also opens up opportunities for further research regarding interventions that can be carried out to improve the organizational climate, so that the quality of employee work can continue to be improved in order to create a better learning environment.